EXTRACURRICULAR MANAGEMENT AT MTsN 1 PESAWARAN LAMPUNG PROVINCE - Junaidah, Junaidah; Zakiyah, Lutfi Maura; Sari, Mayang (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Madrasahs not only have the responsibility and duty to carry out the learning process in developing science and technology, but must maintain and improve both physical and spiritual health. The development of extracurricular activities is very important to be part of the self-development of students in the madrasah. So the management of learner development is a factor that must be taken seriously and must be managed through effective management of learner development. This study aims to describe Extracurricular Management at MTsN 1 Pesawaran with indicators: planning, organizing, implementing and supervising. This research uses a qualitative approach with descriptive research type. The data sources of this research are the Head of Madrasah, head of curriculum, head of student affairs, counseling teacher, extracurricular coaches and students. The data collection techniques were carried out through observation, interviews and documentation. The results of this study indicate that extracurricular management at MTs N 1 Pesawaran through: (1) extracurricular planning which is carried out at the beginning of each new school year, by involving counseling teachers through the “SELAKSA PEMIKAT” wibsite (2) extracurricular organization is carried out based on meetings in each new school year and a decree of the madrasah head which is carried out by extracurricular coaches and trainers by dividing tasks according to their abilities and expertise. (3) extracurricular implementation is carried out according to schedule, with an extracurricular coach approach, (4) extracurricular supervision which is directly supervised by the coach every day and is carried out quarterly by the head of curriculum and head of student affairs, by making reports every week and discussed at the end of the school year. Judging from the extracurricular management process at MTsN 1 Pesawaran, it runs well and is conducive as evidenced by the achievements achieved both at the madrasah, district, provincial and international levels.